Strategic responses to perceived corruption in an emerging market: Lessons from MNEs investing in China - Luo, Yadong (Sage Publications, 2011)
Success in foreign emerging markets is increasingly critical to the global market leadership for many multinational enterprises (MNEs). However, corruption in emerging markets is pervasive and rampant. This study addresses how MNE subunits strategically respond to perceived corruption in the business segment of a foreign emerging market wherein they invest and operate. My analysis suggests that an MNE subunit's investment commitment decreases, and its export market orientation increases, with perceived escalated corruption in the specific business segment. Though perceived corruption in an industrial setting (sectorial corruption) has a stronger effect on the subunit's market orientation, changes in perceived corruption over time (longitudinal corruption) exert a greater influence on investment commitment. To individual subunits, the strength of these strategic responses to corruption is heightened by their ethical awareness but weakened by their indigenous dependence.